Metamaterial inspired re-configurable monopole antenna for RF energy harvesting - Jagadeesan Aswin Babu (2016)
A meta-material inspired re-configurable monopole antenna for RF energy harvesting is proposed in this thesis. The antenna structure consists of a Coplanar Waveguide (CPW) feed which is connected to a rectangular monopole antenna, which is loaded with thin inductor strip and interdigital capacitive (IDC) slot. This introduces metamaterial property in the antenna. Two different antennas are proposed namely one with two IDCs and the other with four IDCs. The goal is to design an antenna for energy harvesting, which requires omnidirectional radiation pattern, and should be functional at wideband/multiband. Hence to be specific the objective is to design, fabricate and test frequency reconfigurable widebandAnultiband antenna. Frequency re-configurability is bought in by switching the introduced diodes at T-IDC slotjunctions which connects and disconnects the IDC slot with the T slot based on the voltage across the diodes, hi case of antenna with two IDCs, it radiates as wideband antenna when IDC slot is connected to the ‘1’ slot, whereas if one is connected and the other is disconnected then it radiates as multiband antenna. In case of antenna with four IDCs different switching combinations give rise to radiation at different frequencies hence leading to frequency re-configurability. The proposed antenna is studied under different switching combinations. Computer Simulation Technology (CST) software was used to design and simulate the proposed antenna. Parametric study was done for optimizing all the important parameters and to understand the working of the antenna. Results were measured and compared with the simulated results and found it to be as expected, except for few cases that were found to be due to fabrication errors. The antenna with two IDCs radiates omnidirectionally between 4.5GHz to 5.5GHz, at 5.35GHz Sn is measured as -8.55dB and the maximum simulated realized gain is 1.939dB when both slots are connected. In the other case antenna radiates as multiband antenna with Sn measured as -11.78dB at 2.1GHz, -10.53dB at 4.36GHz and -16.87dB at 6.9GHz. The maximum simulated realized gain at 4.13GHz was 1.780dB. Whereas in case of antenna with fours IDCs the maximum simulated realized gain with omnidirectional characteristics was found as 1.866dB at 6.97GHz and whereas overall maximum gain was 3.534dB In conclusion a frequency reconfigurable antenna was proposed, simulated and designed. Their reconfigurable property was tested under various switching conditions. The simulated results were compared with the measured results and were found to reasonably comparable and met the design specification for RF energy harvesting, where this antenna can be used in RF energy harvesting system for charging the battery or even for direct power supply to very low power devices.